Examining mindfulness and moral disengagement in doping: Perspective of Turkish wrestlers - Ayyildiz, Erdem; Kayabeşler, Hamza; Gülü, Mehmet; Yagin, Fatma Hilal; Aldhahi, Monira I.; García-Grimau, Elena; Al-Mhanna, Sameer Badri (Frontiers in Psychology, 2023)
Introduction Studies related to attitudes toward the use of prohibited substances in Turkish athletes are scarce. The World Anti-Doping Agency (WADA) has implemented anti-doping educational policies emphasizing doping-related education in studies conducted among Turkish wrestlers. However, it is still unclear the extent to which the wrestlers comply and adhere to these anti-doping policies. No research has previously examined the effect of anti-doping education on athletes' mindfulness and moral disengagement in doping (MDD). Therefore, the present study has a two-fold objective: first, to examine whether doping-related education (DRE) and the status of being a national athlete (NA) have an effect on athlete mindfulness and MDD. Second, to analyze the relationship between each sub-dimensions of athlete mindfulness: awareness (ASD), judgment (JSD), and refocus (RSD) with MDD. Methods A total of 409 male wrestlers participated in this study. MANOVA analysis showed that NA and DRE alone have no effect on MDD but have a general effect on mindfulness. Results The highest effect was on the ASD of being an NA (ηp2 = 0.173). When the interaction effect of NA*DRE was examined, significant difference in MDD (F = 8.218, p = 0.004), ASD (F = 8.476, p = 0.004), JSD (F = 5.844, p = 0.016), and RSD (F = 11.476, p = 0.001) were found. MDD has a weak negative relationship with ASD (r = −0.126) and RSD (r = −0.041) and a weak positive relationship with the JSD sub-dimension (r = 0.140). Those results suggest that being a NA and having received anti-doping education affect moral disengagement in doping and athletes' mindfulness. Discussion As a conclusion, it is recommended to increase awareness and anti-doping education among national-standard Turkish wrestlers to prevent them from engaging in doping behaviors.